Perspektiven auf Vielfalt in der frühen Kindheit Mit Kindern Diversität erforschen 2nd edition - Hedderich, Ingeborg; Reppin, Jeanne; Butschi, Corinne (Verlag Julius Klinkhardt, 2021)
The impetus and aim of this publication is to shed light on different perspectives on diversity in early childhood and to explore possibilities for researching this together with children. Reference is made to bodies of knowledge and knowledge references that have developed and become established in the context of early childhood and diversity, and attention is paid to explaining different methods and concrete experiences of using them to explore perspectives on diversity. One focus is on the description and reflection of research with children. The book is aimed at students and researchers in educational science and its neighbouring disciplines. It gives them an insight into basic theoretical frameworks with regard to the thematic horizons of childhood, childhood research and diversity and presents methods of research that enable the active inclusion of children in a concentrated manner. Furthermore, it gives professionals in elementary education and heads of organisations an impression of methods (reflections) and procedures of research with children and can be a support for them in the context of decision-making processes about participation in research projects.